CaMKII (Ca2+/Calmodulin-Dependent Kinase II) in Mitochondria of Smooth Muscle Cells Controls Mitochondrial Mobility, Migration, and Neointima Formation. Issue 6 (June 2018) - Nguyen, Emily K.; Koval, Olha M.; Noble, Paige; Broadhurst, Kim; Allamargot, Chantal; Wu, Meng; Strack, Stefan; Thiel, William H.; Grumbach, Isabella M.
Abstract : Objective—: The main objective of this study is to define the mechanisms by which mitochondria control vascular smooth muscle cell (VSMC) migration and impact neointimal hyperplasia. Approach and Results—: The multifunctional CaMKII (Ca 2+ /calmodulin-dependent kinase II) in the mitochondrial matrix of VSMC drove a feed-forward circuit with the mitochondrial Ca 2+ uniporter (MCU) to promote matrix Ca 2+ influx. MCU was necessary for the activation of mitochondrial CaMKII (mtCaMKII), whereas mtCaMKII phosphorylated MCU at the regulatory site S92 that promotes Ca 2+ entry. mtCaMKII was necessary and sufficient for platelet-derived growth factor–induced mitochondrial Ca 2+ uptake. This effect was dependent on MCU. mtCaMKII and MCU inhibition abrogated VSMC migration and mitochondrial translocation to the leading edge. Overexpression of wild-type MCU, but not MCU S92A, mutant in MCU − /− VSMC rescued migration and mitochondrial mobility. Inhibition of microtubule, but not of actin assembly, blocked mitochondrial mobility. The outer mitochondrial membrane GTPase Miro-1 promotes mitochondrial mobility via microtubule transport but arrests it in subcellular domains of high Ca 2+ concentrations. In Miro-1 −/− VSMC, mitochondrial mobility and VSMC migration were abolished, and overexpression of mtCaMKII or a CaMKII inhibitory peptide in mitochondria (mtCaMKIIN) had no effect. Consistently, inhibition of mtCaMKII increased and prolonged cytosolic Ca 2+ transients. mtCaMKII inhibition diminished phosphorylation of focal adhesion kinase and myosin light chain, leading to reduced focal adhesion turnover and cytoskeletal remodeling. In a transgenic model of selective mitochondrial CaMKII inhibition in VSMC, neointimal hyperplasia was significantly reduced after vascular injury. Conclusions—: These findings identify mitochondrial CaMKII as a key regulator of mitochondrial Ca 2+ uptake via MCU, thereby controlling mitochondrial translocation and VSMC migration after vascular injury. Abstract : Supplemental Digital Content is available in the text.